Find the square root of \[7-4\sqrt{3}.\]
\[\left( a \right)2+\sqrt{3}\]
\[\left( b \right)5-\sqrt{3}\]
\[\left( c \right)2-\sqrt{3}\]
\[\left( d \right)5+\sqrt{3}\]
Answer
Verified
482.4k+ views
Hint: We have \[7-4\sqrt{3},\] we are asked to find the square root. First, we will rearrange \[7-4\sqrt{3}\] in such a way that it is a square of some term. In order to rearrange, first, we will use \[2=\sqrt{4}\] and then split 7 = 3 + 4 using these. Then we will get \[7-4\sqrt{3}\] as \[{{\left( 2-\sqrt{3} \right)}^{2}}.\] So, taking the square root on both sides, we will get our solution.
Complete step-by-step answer:
So, we are asked to find the square root of \[7-4\sqrt{3}.\] To do so, we will try to write \[7-4\sqrt{3}\] in such a way that it is a square of some numbers by rearranging the terms. Now,
\[2=\sqrt{4}\]
So,
\[7-4\sqrt{3}=7-2\times \left( 2\sqrt{3} \right)\]
\[\Rightarrow 7-4\sqrt{3}=7-2\sqrt{4}\times \sqrt{3}\]
We can write,
\[\sqrt{4}\times \sqrt{3}=\sqrt{12}\]
So, we get,
\[\Rightarrow 7-2\sqrt{12}\]
Now, we will split 7 into 2 terms, i.e. 7 = 3 + 4. Now, putting this in the above term, we will get,
\[\Rightarrow 3+4-2\sqrt{12}\]
We can write 3 as \[{{\left( \sqrt{3} \right)}^{2}}\] and 4 as \[{{\left( \sqrt{4} \right)}^{2}}.\]
And so, we get,
\[\Rightarrow {{\left( \sqrt{3} \right)}^{2}}+{{\left( \sqrt{4} \right)}^{2}}-2\sqrt{12}\]
We can write, \[\sqrt{12}=\sqrt{3}\times \sqrt{4}.\]
\[\Rightarrow {{\left( \sqrt{3} \right)}^{2}}+{{\left( \sqrt{4} \right)}^{2}}-2\times \sqrt{3}\times \sqrt{4}\]
We know that, \[{{a}^{2}}+{{b}^{2}}-2ab={{\left( a-b \right)}^{2}}.\]
So, we get,
\[\Rightarrow {{\left( \sqrt{4}-\sqrt{3} \right)}^{2}}\]
Hence, we have,
\[7-2\sqrt{3}={{\left( \sqrt{4}-\sqrt{3} \right)}^{2}}\]
Also, we know that \[\sqrt{4}=2,\] so we get,
\[\left( 7-2\sqrt{3} \right)={{\left( 2-\sqrt{3} \right)}^{2}}\]
Now taking the square root on both the sides, we get,
\[\Rightarrow \sqrt{7-2\sqrt{3}}=\sqrt{{{\left( 2-\sqrt{3} \right)}^{2}}}\]
On further simplification, we get,
\[\sqrt{7-2\sqrt{3}}=2-\sqrt{3}\]
So, the correct answer is “Option C”.
Note: Another way to look for the square root is, we have 4 options, so we will square each option and see which will end up as \[7-2\sqrt{3}\] and that would be the correct option.
\[\left( a \right)2+\sqrt{3}\]
Squaring \[2+\sqrt{3},\] we get,
\[{{\left( 2+\sqrt{3} \right)}^{2}}={{2}^{2}}+{{\left( \sqrt{3} \right)}^{2}}+2\times \sqrt{3}\times 2\]
\[\Rightarrow {{\left( 2+\sqrt{3} \right)}^{2}}=4+3+4\sqrt{3}\]
\[\Rightarrow {{\left( 2+\sqrt{3} \right)}^{2}}=7+4\sqrt{3}\]
Hence, \[7+4\sqrt{3}\ne 7-4\sqrt{3}\]
Thus, option (a) is not our required answer.
\[\left( b \right)\left( 5-\sqrt{3} \right)\]
Squaring \[\left( 5-\sqrt{3} \right),\] we get,
\[\Rightarrow \left( 5-\sqrt{3} \right)={{5}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-5\times 2\times \sqrt{3}\]
We know that, \[{{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab.\]
\[\Rightarrow \left( 5-\sqrt{3} \right)=25+3-10\sqrt{3}\]
\[\Rightarrow {{\left( 5-\sqrt{3} \right)}^{2}}=28-10\sqrt{3}\]
Hence, \[5-\sqrt{3}\ne 7-4\sqrt{3}\]
Thus, option (b) is not our required answer.
\[\left( c \right)2-\sqrt{3}\]
Squaring \[\left( 2-\sqrt{3} \right),\] we get,
\[{{\left( 2-\sqrt{3} \right)}^{2}}={{2}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-2\times 2\times \sqrt{3}\]
\[\Rightarrow {{\left( 2-\sqrt{3} \right)}^{2}}=4+3-4\sqrt{3}\]
\[\Rightarrow {{\left( 2-\sqrt{3} \right)}^{2}}=7-4\sqrt{3}\]
Hence, \[7-4\sqrt{3}=7-4\sqrt{3}\]
Thus, option (c) is our required answer.
Complete step-by-step answer:
So, we are asked to find the square root of \[7-4\sqrt{3}.\] To do so, we will try to write \[7-4\sqrt{3}\] in such a way that it is a square of some numbers by rearranging the terms. Now,
\[2=\sqrt{4}\]
So,
\[7-4\sqrt{3}=7-2\times \left( 2\sqrt{3} \right)\]
\[\Rightarrow 7-4\sqrt{3}=7-2\sqrt{4}\times \sqrt{3}\]
We can write,
\[\sqrt{4}\times \sqrt{3}=\sqrt{12}\]
So, we get,
\[\Rightarrow 7-2\sqrt{12}\]
Now, we will split 7 into 2 terms, i.e. 7 = 3 + 4. Now, putting this in the above term, we will get,
\[\Rightarrow 3+4-2\sqrt{12}\]
We can write 3 as \[{{\left( \sqrt{3} \right)}^{2}}\] and 4 as \[{{\left( \sqrt{4} \right)}^{2}}.\]
And so, we get,
\[\Rightarrow {{\left( \sqrt{3} \right)}^{2}}+{{\left( \sqrt{4} \right)}^{2}}-2\sqrt{12}\]
We can write, \[\sqrt{12}=\sqrt{3}\times \sqrt{4}.\]
\[\Rightarrow {{\left( \sqrt{3} \right)}^{2}}+{{\left( \sqrt{4} \right)}^{2}}-2\times \sqrt{3}\times \sqrt{4}\]
We know that, \[{{a}^{2}}+{{b}^{2}}-2ab={{\left( a-b \right)}^{2}}.\]
So, we get,
\[\Rightarrow {{\left( \sqrt{4}-\sqrt{3} \right)}^{2}}\]
Hence, we have,
\[7-2\sqrt{3}={{\left( \sqrt{4}-\sqrt{3} \right)}^{2}}\]
Also, we know that \[\sqrt{4}=2,\] so we get,
\[\left( 7-2\sqrt{3} \right)={{\left( 2-\sqrt{3} \right)}^{2}}\]
Now taking the square root on both the sides, we get,
\[\Rightarrow \sqrt{7-2\sqrt{3}}=\sqrt{{{\left( 2-\sqrt{3} \right)}^{2}}}\]
On further simplification, we get,
\[\sqrt{7-2\sqrt{3}}=2-\sqrt{3}\]
So, the correct answer is “Option C”.
Note: Another way to look for the square root is, we have 4 options, so we will square each option and see which will end up as \[7-2\sqrt{3}\] and that would be the correct option.
\[\left( a \right)2+\sqrt{3}\]
Squaring \[2+\sqrt{3},\] we get,
\[{{\left( 2+\sqrt{3} \right)}^{2}}={{2}^{2}}+{{\left( \sqrt{3} \right)}^{2}}+2\times \sqrt{3}\times 2\]
\[\Rightarrow {{\left( 2+\sqrt{3} \right)}^{2}}=4+3+4\sqrt{3}\]
\[\Rightarrow {{\left( 2+\sqrt{3} \right)}^{2}}=7+4\sqrt{3}\]
Hence, \[7+4\sqrt{3}\ne 7-4\sqrt{3}\]
Thus, option (a) is not our required answer.
\[\left( b \right)\left( 5-\sqrt{3} \right)\]
Squaring \[\left( 5-\sqrt{3} \right),\] we get,
\[\Rightarrow \left( 5-\sqrt{3} \right)={{5}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-5\times 2\times \sqrt{3}\]
We know that, \[{{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab.\]
\[\Rightarrow \left( 5-\sqrt{3} \right)=25+3-10\sqrt{3}\]
\[\Rightarrow {{\left( 5-\sqrt{3} \right)}^{2}}=28-10\sqrt{3}\]
Hence, \[5-\sqrt{3}\ne 7-4\sqrt{3}\]
Thus, option (b) is not our required answer.
\[\left( c \right)2-\sqrt{3}\]
Squaring \[\left( 2-\sqrt{3} \right),\] we get,
\[{{\left( 2-\sqrt{3} \right)}^{2}}={{2}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-2\times 2\times \sqrt{3}\]
\[\Rightarrow {{\left( 2-\sqrt{3} \right)}^{2}}=4+3-4\sqrt{3}\]
\[\Rightarrow {{\left( 2-\sqrt{3} \right)}^{2}}=7-4\sqrt{3}\]
Hence, \[7-4\sqrt{3}=7-4\sqrt{3}\]
Thus, option (c) is our required answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science